Preparação e Caracterização de Materiais Orgânicos com Potencial Aplicação em Dispositivos Fotovoltaicos - Klider, Karine Cristina Carrilho Weber dos Santos (2010)
The introduced work on this dissertation discussion presented in this master’s degree dissertation describes the development of a synthetic rote to obtain a compound that contains an aromatic ring and connected to it two dibromade methyl groups, a CN group and a dye. The dye used at this work was the Rhodamine B, and the final product consists on a monomer that when gets polymerized, by electrochemical route, produces a luminescent polymer to solar cell application. It was described the preparation and the characterization of a series of organic compounds. Some intermediary compounds were prepared after the realization of a lot of steps of synthesis to finally approach the best methodology. The compounds characterization were performed by means of infrared spectroscopic (FTIR) and nuclear magnetic resonance spectroscopic measurements (RMN H1). Another part of this work describes a soluble copolymer preparation by electrochemical rote and it characterization. The prepared copolymer consists on the soluble form of a mixture of poly(2-methoxy-5-bromo-p-phenylenevinylene) (MBPPV) and poly(2,5-dicyano-p-phenylenevinylene) DCN-PPV at different proportion. The copolymer DCN-PPV/MB-PPV and the polymer MB-PPV were synthesized by electrochemical rote and the charges transfer process were studied by cyclic voltammetry and chronoamperometry measurements. These copolymers were characterized by FTIR and UV-VISIBLE absorption spectroscopy and by measurements of fluorescence.